AN IMPROVEMENT OF INTEGRATED GEOGRAPHICAL INFORMATION SYSTEM IN MANAGING SEWERAGE TREATMENT PLANT - Idris, Muhamad Zuraini; Suratman, Robiah; Samsuddin, Salfarina (PLANNING MALAYSIA, 2021)
In Malaysia, the Geographical Information System (GIS) is widely used by various organizations in both government and private sectors because of its various capabilities. The rapid development process in the large city in Peninsular Malaysia and new area has caused an increasing number of the sewerage treatment plant (STP) maintained by Indah Water Konsortium Sdn Bhd (IWK) every year. Nowadays, with the big services areas and limited staffs the IWK had faced many issues related to the sewerage such as a public complaint on blockage, overflow and others. Thus, based on the powerful function of this GIS, the IWK also has used the GIS application known as Integrated Geographical Information System (IGIS) in their daily routine works. However, due to the weaknesses of this existing system, it cannot be optimally utilized in managing and maintaining the sewerage system more efficient. The main objective of this research focuses on analyzing user requirements to improve IGIS based on the current issues faced by them. The method used in this study is qualitative method using a face-to-face interview with IGIS users in getting any feedback from them on the existing data with an examining what is the main attribute data required. Then a content analysis was used to analyze it by updating all the data required and removing unnecessary data from the IGIS. As a result, the newly updated attribute data into IGIS will help the users to conduct proper planning in controlling the increasing number of STP every year and to manage the sewerage system more efficiently.